2014
DOI: 10.1038/srep04941
|View full text |Cite
|
Sign up to set email alerts
|

Learning from the past: Rare ε-Fe2O3 in the ancient black-glazed Jian (Tenmoku) wares

Abstract: Ancient Jian wares are famous for their lustrous black glaze that exhibits unique colored patterns. Some striking examples include the brownish colored “Hare's Fur” (HF) strips and the silvery “Oil Spot” (OS) patterns. Herein, we investigated the glaze surface of HF and OS samples using a variety of characterization methods. Contrary to the commonly accepted theory, we identified the presence of ε-Fe2O3, a rare metastable polymorph of Fe2O3 with unique magnetic properties, in both HF and OS samples. We found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
84
2
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 110 publications
(114 citation statements)
references
References 33 publications
12
84
2
8
Order By: Relevance
“…Although the vibration modes of ε-Fe 2 O 3 have not yet been clearly described, the observation of this phase was recently reported on an ancient Jian wares. Indeed, Dejoie et al [59] showed by TEM/EDX and XRD analyses the presence of this rare metastable polymorph of Fe 2 O 3 while Raman spectra were collected on large and small crystal clusters. The present Raman spectra, without the maghemite vibration modes, show similarities to those reported by these authors, in particular in the vicinity of the 200–800 cm −1 range.…”
Section: Discussionmentioning
confidence: 99%
“…Although the vibration modes of ε-Fe 2 O 3 have not yet been clearly described, the observation of this phase was recently reported on an ancient Jian wares. Indeed, Dejoie et al [59] showed by TEM/EDX and XRD analyses the presence of this rare metastable polymorph of Fe 2 O 3 while Raman spectra were collected on large and small crystal clusters. The present Raman spectra, without the maghemite vibration modes, show similarities to those reported by these authors, in particular in the vicinity of the 200–800 cm −1 range.…”
Section: Discussionmentioning
confidence: 99%
“…This issue causes to neglect its presence in any geophysical model of the Earth’s structure so far. However, the recent findings of this compound in plants 29 in a non-negligible amount (about 10% of the total amount of minerals), the discovery of this material as fundamental part of ancient black-glazed Jian wares 31 , as well as the discovery of a isostructural Al-bearing ε-Fe 2 O 3 mineral (Luogufengite) 32 possibly formed by thermal decomposition of almandine garnet and iron-rich clays in the Earth crust, upper mantle, and transition zone 33 , triggered our interest to investigate its stability range at high pressures (HP) and its possible influence in the Earth’s geodynamic. Moreover, ε-Fe 2 O 3 has showed to be highly stable at high temperatures, being the HT polymorph of maghemite 28 above 700 C, and remaining stable up to 1100 C (synthesis conditions) or higher, 1400 C 25 .…”
Section: Introductionmentioning
confidence: 99%
“…A rare and metastable ferric oxide polymorph (ε-Fe 2 O 3 ) has just been discovered in ancient Chinese ceramics (Dejoie et al 2014). Identified in 1934, this phase keenly interests the materials science community for its promising applications in the fields of electronic storage media and magnetic stripe cards.…”
Section: Iron Oxides In Black Glazed Chinese Ceramicsmentioning
confidence: 99%
“…Much less prevalent, the variety called "oil spot" was also sought for its silvery glints. Recently, one fragment of each variety was analysed using a set of characterization techniques including micro X-ray fluorescence and micro X-ray diffraction synchrotron, Raman spectroscopy and transmission electron microscopy (Dejoie et al 2014). It was established that the coloured patterns were due to the crystallization of iron oxides in the glaze surface (Li et al 2008), but without considering that the predominant form was ε-Fe 2 O 3 .…”
Section: Iron Oxides In Black Glazed Chinese Ceramicsmentioning
confidence: 99%